2014
DOI: 10.1007/s10143-014-0525-y
|View full text |Cite
|
Sign up to set email alerts
|

Invasive adenoma and pituitary carcinoma: a SEER database analysis

Abstract: Invasive pituitary adenomas and pituitary carcinomas are clinically indistinguishable until identification of metastases. Optimal management and survival outcomes for both are not clearly defined. The purpose of this study is to use the Surveillance, Epidemiology, and End Results (SEER) database to report patterns of care and compare survival outcomes in a large series of patients with invasive adenomas or pituitary carcinomas. One hundred seventeen patients diagnosed between 1973 and 2008 with pituitary adeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 28 publications
4
59
0
4
Order By: Relevance
“…Besides that Novruzov F et al found that peptide receptor radiotherapy with 117 Lu DOTATATE has shown to be effective in stopping pituitary carcinoma growth for more than 4 years [7]. However, there is no clinical trialbased data have demonstrated that traditional radiotherapy is effective in improving survival in patients with pituitary carcinoma [8]. Radiotherapy was also used in this patient, but it did not control the regrowth of the tumor.…”
Section: Discussionmentioning
confidence: 89%
“…Besides that Novruzov F et al found that peptide receptor radiotherapy with 117 Lu DOTATATE has shown to be effective in stopping pituitary carcinoma growth for more than 4 years [7]. However, there is no clinical trialbased data have demonstrated that traditional radiotherapy is effective in improving survival in patients with pituitary carcinoma [8]. Radiotherapy was also used in this patient, but it did not control the regrowth of the tumor.…”
Section: Discussionmentioning
confidence: 89%
“…A recent review of the SEER database found at total of 117 cases diagnosed between 1973 and 2008. 9 Specifically, data from 83 atypical pituitary adenomas and 7 pituitary adenocarcinomas were used to compare survival and treatment outcomes. This review found worse survival in patients with pituitary carcinoma than in patients with atypical, invasive adenoma.…”
Section: Treatment Outcome and Prognosismentioning
confidence: 99%
“…Предпринимались попытки определить особенности морфологического строения и молекулярные маркеры, чаще ассоциирующиеся с ин вазивными аденомами или карциномами гипофиза, для прогнозирования поведения опухоли и дифферен циальной диагностики до выявления метастазов. Они включали количественную оценку степени цитологи ческой атипии и митотической активности, изучение распространения маркеров, таких, как Ki67, с исполь зованием MIB1 антител и молекул клеточного цикла р27 и галектин3, экспрессию гена р53, мутации N, K, Hras протоонкогенов [7,[10][11][12][13][14]. Например, отмечено повышение индекса MIB1 антител у карциномы (12 %) по сравнению с инвазивными аденомами (4,5 %) и неинва зивными аденомами (1 %) [15].…”
Section: обсуждение результатовunclassified
“…В другом исследовании не обнаружены мутации гена -супрессора опухоли р53 или N, Kras протоонкогенов, но идентифицированы точечные мутации в Нras гене [17]. Несмотря на такие выводы, в настоящее время не выяв лено однозначных гистологических, иммуногистохими ческих и молекулярногенетических маркеров, которые отличают инвазивные аденомы гипофиза от карцином [6,14,18]. В описанном нами случае индекс Ki67 в первич ной опухоли составил 10-15 %, а в метастазе правой пле чевой кости -5-6 %.…”
Section: обсуждение результатовunclassified